2023
DOI: 10.1002/cbic.202300453
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Photoswitchable Binding Interactions with Small‐Molecule‐ and Peptide‐Based Inhibitors of Trypsin

Abstract: The ability to photochemically activate a drug, both when and where needed, requires optimisation of the difference in biological activity between each isomeric state. As a step to this goal, we report small molecule and peptide‐based inhibitors of the same protease – trypsin – to better understand how photoswitchable drugs interact with their biological target. The best peptidic inhibitor displayed a >5‐fold difference in inhibitory activity between isomeric states, whereas the best small molecule inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The fold difference in activity was modest with values up to 2.2. [77] Another photo-induced ring opening reaction that influences the activity against chymotrypsin was reported by Pal and colleagues. They reported that the dihydroindolizine scaffold 14, and the UV-induced ring-opened compound 15 (Figure 9A) both inhibit chymotrypsin, but to a different extent.…”
Section: Photoswitchable Inhibitors For S1 Family Proteasesmentioning
confidence: 90%
See 3 more Smart Citations
“…The fold difference in activity was modest with values up to 2.2. [77] Another photo-induced ring opening reaction that influences the activity against chymotrypsin was reported by Pal and colleagues. They reported that the dihydroindolizine scaffold 14, and the UV-induced ring-opened compound 15 (Figure 9A) both inhibit chymotrypsin, but to a different extent.…”
Section: Photoswitchable Inhibitors For S1 Family Proteasesmentioning
confidence: 90%
“…Note that these do not contain an electrophile that binds the active site serine of the targeted trypsin. The fold difference in activity was modest with values up to 2.2 [77] …”
Section: Photoactivatable Protease Inhibitorsmentioning
confidence: 92%
See 2 more Smart Citations